2023
DOI: 10.1002/ohn.314
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Preoperative DOI Estimation in Oral Tongue Cancer With cN0 Disease

Abstract: ObjectiveTo understand the accuracy of pre‐ and intraoperative estimation of tumor depth of invasion (DOI).Study DesignA retrospective case‐control study.SettingPatients who presented at 1 institution with oral tongue squamous cell carcinoma that underwent oncologic resection between 2017 and 2019 were identified.MethodsPatients that met the inclusion criteria were included. Patients with nodal, distant, or recurrent disease, prior history of head and neck cancer, or preoperative tumor assessment and/or final … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Two studies made comparisons between IOUS and histopathology regarding the deep margin. 16,19,23,25,32 Songra et al reported a Pearson correlation coefficient of 0.648 (P < .01) between the deep margin measured by IOUS and histopathology. 16 Baek et al compared the deep margin clearance in IOUS-assisted resection cases to that of conventional resection, and a student's t test revealed a significant difference favoring IOUS-assisted resection (P < .001).…”
Section: Ious Measurements Correlate With Final Histopathologymentioning
confidence: 99%
“…Two studies made comparisons between IOUS and histopathology regarding the deep margin. 16,19,23,25,32 Songra et al reported a Pearson correlation coefficient of 0.648 (P < .01) between the deep margin measured by IOUS and histopathology. 16 Baek et al compared the deep margin clearance in IOUS-assisted resection cases to that of conventional resection, and a student's t test revealed a significant difference favoring IOUS-assisted resection (P < .001).…”
Section: Ious Measurements Correlate With Final Histopathologymentioning
confidence: 99%
“…Full text analysis was performed on the remaining 33 articles, and 17 articles were further excluded. The final review included 16 articles [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], which all met the criteria for inclusion in the meta-analysis (Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…In 13 studies [13,[15][16][17][20][21][22][23][24][25][26][27][28], ultrasonography was performed preoperatively. The frequencies employed ranged between a minimum of 5 and a maximum of 70 MHz (Table 1).…”
Section: Population and Studies Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to full-thickness biopsies [15], US has diagnostic value for small OSCC. However, in the case of extensive tumors, these methods do not demonstrate high DOI imaging efficiency.…”
Section: Introductionmentioning
confidence: 96%